Association of CYP24A1 gene polymorphism with colorectal cancer in the Jiamusi population. - Lin Chai; Jian Ni; Xiaolin Ni; Nan Zhang; Yang Liu; Zhiwu Ji; Xingwang Zhao; Xiaowen Zhu; Bin Zhao; Guorong Xin; Yu Wang; Fan Yang; et al. (PLoS ONE, 2021)
Background The population in Jiamusi has been reported to have the highest prevalence of colorectal cancer (CRC) in China. The genetic causal-effect for this occurrence among the residents remains unclear. Given the long cold seasons with people wearing more clothes and reduced UV exposure, we aimed to study the association between the vitamin D metabolism-related gene CYP24A1 polymorphism and CRC susceptibility. Method A case-control study was conducted that included 168 patients with CRC and 710 age-matched healthy individuals as the control group. Plausible susceptible variations were sought and clinical phenotypic-genotype association analysis was performed. Results Overall, two CYP24A1 polymorphisms, rs6013905 AX (P = 0.02, OR = 1.89, 95%CI: 1.09-3.29) and rs2762939 GX (P = 0.02, OR = 1.52, 95%CI: 1.08-2.13) were significantly associated with CRC in the Jiamusi population. In the female group, three CYP24A1 polymorphisms, rs6013905 AX (P = 0.04, OR = 2.59, 95%CI: 1.03-6.49), rs2762939 GX (P = 0.01, OR = 2.35, 95%CI: 1.25-4.42), and rs6068816 GG (P = 0.05, OR = 1.89, 95%CI: 0.99-3.59) carriers were significantly associated with CRC. In clinical phenotypic-genotype analysis, rs6013905 GG (P = 0.05, OR = 4.00, 95%CI: 0.92-17.48) and rs2762939 GX (P = 0.03, OR = 4.87, 95%CI: 1.00-23.69) carriers were significantly associated with poorly differentiated CRC, while CYP24A1 rs6068816 AX was significantly associated with the tumor type (P = 0.02, OR = 2.08, 95%CI: 1.10-3.96) and location (P = 0.04, OR = 2.24, 95%CI: 1.05-4.77). Conclusion CYP24A1 gene polymorphism may be a genetic risk factor attributable to the highest prevalence of CRC in Jiamusi people. Individuals with CYP24A1 gene polymorphism may have an increased barrier for vitamin D absorption, thus contributing to the risk of CRC development.